Arbutin improves gut development and serum lipids via Lactobacillus intestinalis - Ma, Jie; Chen, Shuai; Li, Yuying; Wu, Xin; Song, Zehe (Frontiers in Nutrition, 2022)
Arbutin has been widely studied in whitening, anti-inflammatory and antioxidant. However the interaction between arbutin and intestinal microbes has been rarely researched. Thus, mice were treated with arbutin concentrations of 0 mg/ml,0.1 mg/ml, 0.2 mg/ml, 0.4 mg/ml and 1mg/ml. We found that arbutin promoted the gut development such as villus length, villus areas and villus length/crypt depth (L/D). And total cholesterol (TC), heigh-density lipoprotein (HDL) and low-density lipoprotein (LDL) were significantly reduced by low concentrations of arbutin. Importantly, We analyzed the microbial composition in the control and 0.4mg/ mL arbutin group and found that the abundance of Lactobacillus intestinalis was heihgest and enhanced in arbutin. Futher, mice were oral antibiotics and antibiotics + 0.4mg/ mL arbutin and then we we transplanted fecal microbes from oral 0.4 mg/mL arbutin mice to mice pretreated with antibiotics. our results showed that arbutin improves gut development,sunch as villus width ,villus length, L/D and villus areas.. In addition, L. intestinalis mono-colonization was carred out after a week of oral antibiotics and increased villus length, crypt depth and villus area, Finally, in vitro arbutin and L. intestinalis co-culture showed that arbutin promoted the growth and proliferation of L. intestinalis. Taken together, our results suggest that arbutin improves gut development and health by L. intestinalis. Future studies are needed to explore the function and mechanism of L. intestinalis affecting gut development.